2020
DOI: 10.1103/physrevb.102.134305
|View full text |Cite
|
Sign up to set email alerts
|

hErMnO3 absorbance, reflectivity, and emissivity in the terahertz to mid-infrared from 2 to 1700 K: Carrier screening, Fröhlich resonance, small polarons, and bipolarons

Abstract: We report the temperature dependent THz to mid-infrared response of hexagonal-ErMnO3 using absorption, reflectivity, and emissivity techniques from 2 K to 1700 K. At low temperatures, lowest frequency vibrational modes which extend up the lock-in ferroelectric temperature, coexist with paramagnon excitations and are associated with well-defined crystal field Rare Earth pure magnetic replicas in an intriguing phonon-magnetic convergence enhancing the multiferroic character of h-ErMnO3. Increasing the temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…According to previous studies, the resonance absorption in the 0.4–0.8 THz range represents the polarization of the [MnCl 2 O 4 ] unit. 30 In our experiments, we observed that within the temperature range of 180–320 K, the resonance absorption of [MnCl 2 O 4 ] gradually increases with temperature, but the magnitude of the increase is small. The enhancement of resonance absorption corresponds to a weakening of polarization intensity, consistent with our computational results (Fig.…”
mentioning
confidence: 54%
“…According to previous studies, the resonance absorption in the 0.4–0.8 THz range represents the polarization of the [MnCl 2 O 4 ] unit. 30 In our experiments, we observed that within the temperature range of 180–320 K, the resonance absorption of [MnCl 2 O 4 ] gradually increases with temperature, but the magnitude of the increase is small. The enhancement of resonance absorption corresponds to a weakening of polarization intensity, consistent with our computational results (Fig.…”
mentioning
confidence: 54%
“…The functional property of ErMnO3 that has attracted attention as having greatest potential for use in device applications is the electrical conductivity of domain walls [4,29,31,33,49,[67][68][69][70][71]. For some of the aspirations in this context to be achieved, it will be necessary to engineer domain walls into preferred configurations and then constrain the chosen microstructure to remain stable during long term operation of the device.…”
Section: Engineering Of Microstructuresmentioning
confidence: 99%
“…Members of the family of multiferroic hexagonal manganites, RMnO3 (R = Sc, Y, In, Dy-Lu), are ferroelectric due to a structural phase transition within the interval ~1000-1500 K [1][2][3][4][5] and antiferromagnetic due to a magnetic ordering transition within the interval ~60-130 K [6][7][8][9][10]. Their structures at high temperatures and at room temperature are in space groups P63/mmc and P63cm, respectively [3,5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%